Outflow of Nepali Migrants and Its Future Impact on Society (Surkhet Journal, 2025)
This paper analyzes the impact of the constant outflow of migration to the international labor market and its immediate and ultimate impacts on society. The main aim of this study was that migrant workers and origin countries might be financially benefited but ultimately, regular mobility of labor migrants beyond the country it has cumulative losses and which couldn't be compensated for native country. The changing geopolitical and economic dimensions rotate on different angles and create new circumstances as a big threat and challenges to address the problem for migrant workers. A significant proportion of productive Nepali citizens have already left their native country and new generation has learnt foreign languages and go abroad for foreign employment. The result shows it would be increased in the next some years. Short-term impact of labour migration, returnee migrants are returned with lots of inspiration, knowledge, skill, experience and financial resources they can contribute to the nation by mobilizing their own resources and creating jobs paying tax for the nation. It has played several positive roles in the Nepali economy like the reduction of poverty and unemployment, maintaining foreign exchangereserves and correcting the balance of payments.